FATIGUE IN CANCER PATIENTS RECEIVING CHEMOTHERAPY - M. Farajollahi; M. Alikhani; F. Farmani; F. Hosseini (Iran University of Medical Sciences, 2004)
Fatigue is one of the most common and a distressing side effect of cancer and its treatments. It can affect all aspects of patients' life and leads to several other hardships. To determine fatigue intensity and it's changing pattern among those suffering from cancer receiving chemotherapy, a descriptive longitudinal study was conducted. The principal method of data collection was a daily diary, with 28 visual analogue scales (Rhoten Fatique scale). Contributors were 120 cancer patients, receiving chemotherapy. The results indicated that all patients experienced fatigue during their chemotherapy cycles. The pattern of fatigue intensity showed alteration in fatigue scores through a chemotherapy cycle with apparent peak on the fifth day of the cycle. There was a significant relationship between the site of cancer and the level of recorded fatigue ( = 20/98, df=10, P=0/021).A meaningful relationship was identified between the number of chemotherapy cycles and the level of recorded fatigue ( =50/63, df=7, P<0/0001), but there was not a significant relationship between the chemotherapy regimens and the level of recorded fatigue ( = 12/65, df= 9, P= 0/179). To conclude, Findings showed that chemotherapy was associated with fatigue, and different scores were related to the site of cancer and the number of chemotherapy cycles. Therefore, recommendation is made about assessment and management of fatigue in these patients.